2017
DOI: 10.5489/cuaj.4308
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal ultrasound-guided biopsy for prostate cancer detection: Systematic and/or magnetic-resonance imaging-targeted

Abstract: Introduction: Magnetic resonance imaging (MRI) is being more widely used in the detection of prostate cancer (PCa), particularly after an initial negative biopsy. In this study, we compared 12-core systematic biopsy (SYS), MRI-targeted biopsy (TAR), and the association of systematic and MRI-targeted (SYS+TAR) prostate biopsy in patients with previous biopsy and those who were biopsy-naive to evaluate the differences in terms of cancer detection and clinically significant cancer detection between the three moda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Magnetic resonance imaging of the prostate might be a method that can enhance diagnostics, particularly if this is done in connection with the biopsies. It may be able to detect more potentially serious cancers, detect less low risk cancers and reduce unnecessary biopsies [8][9][10]16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging of the prostate might be a method that can enhance diagnostics, particularly if this is done in connection with the biopsies. It may be able to detect more potentially serious cancers, detect less low risk cancers and reduce unnecessary biopsies [8][9][10]16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, magnetic resonance imaging targeted (MRTtargeted biopsies) vs SYS have been compared. MRT-targeted biopsy, when added to SYS, was associated with a higher detection rate of clinically significant cancer in biopsy-naive patients when compared to SYS alone [8]. Siddiqui et al [9] found that MRT/Ultrasound-fusion-guided biopsy upgrades and detects prostate cancer of higher Gleason grade in 32% of patients when compared to 12-core biopsy alone.…”
Section: Introductionmentioning
confidence: 99%
“…Modern prostate biopsy techniques are based on the computerised 3D merging of the ultrasound and MRI images to provide better vision during the procedure (Fusion Biopsy) [ 9 , 10 ]. However, the method is expensive due to high equipment costs.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical routine, the 12-core systematic biopsy (SBx) procedure guided by transrectal ultrasound work as the gold standard for PCa diagnosis. However, biopsies suffer from a risk of infection, the underdiagnosis of significant PCa, and overtreatment of insignificant cancer [2], [3]. Improving the diagnostic efficacy of SBx or even replacing SBx with non-invasive imaging diagnostics tools is in demand.…”
Section: Introductionmentioning
confidence: 99%